Do Neighborhood Characteristics in Amsterdam Influence Adiposity at Preschool Age? - Hrudey, E. Jessica (Int J Environ Res Public Health, 2015)
Background: Neighborhood characteristics may contribute to adiposity in young children, but results in the current literature are inconsistent. This study aimed to investigate whether objective (socioeconomic status (SES)) and subjective (perceived safety, satisfaction with green spaces and perceived physical disorder) neighborhood characteristics directly influence child adiposity (as measured by BMI, percent body fat (%BF) and waist-to-height ratio (WHtR)). Methods: Data on child BMI, %BF and WHtR were obtained from the Amsterdam Born Children and their Development cohort at 5–6 years of age. Three thousand four hundred and sixty nine (3469) children were included in the analyses. Mixed models, using random intercepts for postal code area to account for neighborhood clustering effects, were used to analyze the relationships of interest. Results: Associations were observed for both perceived safety and neighborhood SES with %BF after adjustment for maternal education and ethnicity. All relationships were eliminated with the inclusion of individual covariates and parental BMI into the models. Conclusions: In general, child adiposity at age 5–6 years was not independently associated with neighborhood characteristics, although a small relationship between child %BF and both neighborhood SES and perceived safety cannot be ruled out. At this young age, familial and individual factors probably play a more important role in influencing child adiposity than neighborhood characteristics.